Penyuluhan Anti Bullying Bagi Anak Panti Asuhan Aisyiah Jagakarsa Jakarta Selatan - Haqi Muhammad Diftar; Aqidah Suci Islami; Yutia Wirma; Marissa Anggi Harahap; Agistiana Wiji Musthopa; Reny Andriyanty (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2026)
The effective way to foster empathy and prevent bullying is by conducting educational sessions on bullying. One group particularly vulnerable to bullying is orphaned children. Due to their limited resources, orphaned children are more likely to endure bullying without knowing how to prevent it or protect themselves. This community service activity was aimed at children at the Aisyiah orphanage aged 7–11 years. The objectives of this activity were: 1) to provide children with a basic understanding of what bullying is and the forms of bullying behavior that can occur in daily life, and 2) to raise children’s awareness of the negative impacts of bullying—both on victims and perpetrators—through engaging and easy-to-understand educational sessions. The results of this community service activity indicated an increase in the participants’ understanding. Before the program, only 60% of the orphanage children had adequate knowledge about bullying, but after the session, that figure rose sharply to 95%.